Perancangan dan implementasi e-posyandu untuk peningkatan pelayanan kader di posyandu delima berbasis web - Muhasshanah Muhasshanah; Abd. Ghofur; Fatimatuzzahra Fatimatuzzahra (LPPMPK - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2022)
The problem found was ineffective service because the information was not appropriately conveyed to the parents of toddlers because the cadres did the recording and counting manually. Age calculations were carried out every month by cadres using a specific formula. In addition, determining nutritional status was also done manually by matching the examination data with the Z-score table according to the sex, weight, and height of each toddler. Due to limited human resources, this was often not done, so the nutritional status of toddlers was not filled, and parents did not know for sure the nutritional status of their toddlers. Solution provided by implementing an information system referred to as e-posyandu. E-posyandu can display a recapitulation of toddler examinations in real-time, which can be monitored directly by the responsible local health center midwife. The implementation method in this study is divided into several stages: problem identification, system design, information system development, and implementation. The results obtained are that e-posyandu can assist Posyandu Delima cadres in recording development and growth digitally, thus facilitating and improving the quality of cadre services in carrying out posyandu checks can also help parents to monitor the results of the toddlers' development and growth